Mining Sudanese Medicinal Plants for Antiprotozoal Agents - Mahmoud, Abdelhalim Babiker; Mäser, Pascal; Kaiser, Marcel; Hamburger, Matthias; Khalid, Sami (Frontiers in Pharmacology, 2020)
Neglected tropical diseases are major health hazards in developing countries. Annually, up to thirty million people are affected by either Chagas disease, African trypansomiasis or leishmaniasis, and more than 200 million by malaria. Most of the currently available drugs have drawbacks in terms of toxicity, limited oral availability, development of resistance, or non-affordability. Tropical plants of the arid zones are a treasure chest for the discovery of bioactive secondary metabolites. This study aims to compile Sudanese medicinal plants, validate their antiprotozoal activities, and identify active molecules. We have performed a survey of medicinal plants of Sudan and selected 62 that are being used in Sudanese traditional medicine. From these, we collected materials such as leaves, stem, bark, or fruit. The plant materials were extracted in 70% ethanol and further fractionated by liquid-liquid partitioning using solvents of increasing polarity. This resulted in a library of 235 fractions. The library was tested in vitro against Plasmodium falciparum (erythrocytic stages), Trypanosoma brucei rhodesiense (bloodstream forms), Trypanosoma cruzi (intracellular amastigotes), and Leishmania donovani (axenic amastigotes). Active fractions were also tested for cytotoxicity. Of the 235 fractions, 125 showed growth inhibitory activity >80% at 10 μg/ml, and >50% at 2 μg/ml against at least one of the protozoan parasites. Plasmodium falciparum was the most sensitive of the parasites, followed by T. b. rhodesiense and L. donovani. Only few hits were identified for T. cruzi, and these were not selective. Contrary to expectation based on phylogeny, but in agreement with previous results, a large number of extracts displayed mutual activity against T. brucei and P. falciparum. HPLC-based activity profiling for selected active extracts was performed to identify the bioactive principles. Active compounds identified by dereplication were guieranone A from Guiera senegalensis; pseudosemiglabrin from Tephrosia apollinea; ellagic acid and quercetin from Anogeissus leiocarpus; and catechin, ethyl gallate, and epicatechin gallate from Acacia nilotica. Also the extracts of Croton zambesicus Müll.Arg. and Cuscuta hyalina Roth exhibited promising antitrypanosomatid activity. This assessment provides a comprehensive overview of Sudanese medicinal plants and supports the notion that they are a potential source of bioactive molecules against protozoan parasites.